If it's not what You are looking for type in the equation solver your own equation and let us solve it.
u in (-oo:+oo)
6*((1/2)*u-(2/3)) = 0
6*((1/2)*u-2/3) = 0
6*(1/2*u-2/3) = 0
( 1/2*u-2/3 )
1/2*u-2/3 = 0 // + 2/3
1/2*u = 2/3 // : 1/2
u = 2/3/1/2
u = 4/3
( 6 )
6 = 0
u belongs to the empty set
u = 4/3
| 1/2x^2-6=0 | | 7x-3(3x+17)=-37 | | 2x-2+x=x-24 | | Cot/cos=CDC | | -9x-3y=7 | | 10x+26x-10=9(4x+10) | | 3(4-6y)+7=-1 | | M/9--213=231 | | 12.1=p+2.3 | | X-(156-X)=78 | | 3x-24+2x=2x | | 38x+85=38x+78 | | x2=49/81 | | 5x+4(-3x-10)=103 | | 3/4(2x–8) | | X/-1/6=6/7 | | x^2+4x-8y+12=0 | | -5(f-929)=85 | | P+2p+3p+2=2 | | 7x+23x-4=6(5x+9) | | 18(w+25)=468 | | 4x-2(1+2x)=6 | | 3.4w=9.7 | | 34x+3y=12 | | 2x(-40)=x | | 0.8k=1.36 | | 3=w-5/4 | | f(1)=-12 | | a+3b=4ab | | -2a-3a+1=6 | | 356/16=267/x | | -2x+4x-28=-2x+3x-12 |